The given function g(x) = 4x² + 11x +6 is already in its general form in which the value of a = 4, b = 11, and c = 6. We will needing these values in the quadratic formula.
The formula is:
![x=(-b\pm√(b^2-4ac))/(2a)](https://img.qammunity.org/2023/formulas/mathematics/college/jr19ixi2zltkocy82qhxfiop5lyv4hzbkm.png)
Let's plug into the formula above the values of a, b, and c.
![x=(-11\pm√(11^2-4(4)(6)))/(2(4))](https://img.qammunity.org/2023/formulas/mathematics/college/quurz04uybcxzg5b954qew571z7wl4lkon.png)
Then, solve.
a. Simplify the numbers inside the parenthesis.
![x=(-11\pm√(121-96))/(2(4))\Rightarrow x=(-11\pm√(25))/(2(4))](https://img.qammunity.org/2023/formulas/mathematics/college/pabc40bwofadq7y9yu0gv1vxwff5g6frw8.png)
b. Get the square root of 25 and simplify the denominator.
![x=(-11\pm5)/(8)](https://img.qammunity.org/2023/formulas/mathematics/college/x86a20soyw9ijirnwwk2ymjt2f2aglynbo.png)
c. Separate the plus and minus symbol and solve.
![\begin{gathered} x=(-11+5)/(8)\Rightarrow x=(-6)/(8)\Rightarrow x=-(3)/(4) \\ x=(-11-5)/(8)\Rightarrow x=(-16)/(8)\Rightarrow x=-2 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/z2jvn9pwlctee2kyoyub93mjpee3mr1vdc.png)
The zeros and x-intercepts are the same. They are -3/4 and -2.